1981
DOI: 10.1172/jci110063
|View full text |Cite
|
Sign up to set email alerts
|

Separate Mechanisms of Deformability Loss in ATP-depleted and Ca-loaded Erythrocytes

Abstract: A B S T R A C T Membrane rigidity has been widely accepted as the dominant cause of reduced deformability both of ATP-depleted erythrocytes and erythrocytes containing excess calcium (Ca). However, recent studies have shown normal membrane deformability in ATP-depleted erythrocytes. In addition, Ca accumulation causes massive ion and water loss, and it has been shown that extensive dehydration causes an increase in intracellular viscosity with attendant loss of whole cell deformability. To obtain a detailed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…Echinocyte formation in erythrocytes induced by Ca 2 § loading with the ionophore A23187 with concomitant loss of the whole-cell deformability in flow has been extensively studied [4,26]. Similar findings have been reported for ghosts prepared from cells loaded with various Ca 2+ concentrations of the order of I mM or higher, and the loss of deformability was explained by transglutaminase-mediated protein cross-linking [8].…”
Section: Effect Of Ca 2+ Ionssupporting
confidence: 60%
“…Echinocyte formation in erythrocytes induced by Ca 2 § loading with the ionophore A23187 with concomitant loss of the whole-cell deformability in flow has been extensively studied [4,26]. Similar findings have been reported for ghosts prepared from cells loaded with various Ca 2+ concentrations of the order of I mM or higher, and the loss of deformability was explained by transglutaminase-mediated protein cross-linking [8].…”
Section: Effect Of Ca 2+ Ionssupporting
confidence: 60%
“…The best known of these are: microcytosis secondary to passive efflux of potassium and water (13,15,42); echinocytosis secondary to ATP depletion, 1,2-diacylglycerol accumulation and membrane vesiculation (43,44); sickling secondary to cross-linking of membrane proteins (45), and inhibition of the sodium-potassium pump resulting in intracellular accumulation of sodium (46). The similarity of effects between A23187, a Ca ionophore and BSs in increasing Ca uptake and inducing hemolysis, as demonstrated by this and other studies, raises the possibility that the hemolytic actions of both agents are related (13,36,44,47). In this regard, one possible mechanism of hemolysis associated with either A23187-or BS-induced Ca uptake is increased osmotic fragility.…”
Section: Discussionmentioning
confidence: 99%
“…Noji et al use several different stomatocytogenic calmodulin inhibitors to prevent loss of erythrocyte deformability induced by ionophore-stimulated intracellular calcium overload (Noji et al, 1987). Clark et al (1981) have suggested that ATP depletion causes impaired deformability by indirectly leading to membrane damage while calcium infusion produces the same effect by increasing the cell's internal viscosity by osmotic changes; nevertheless, treatment with stomatocytogenic agents appears to counteract the impairment of deformability under either circumstance.…”
Section: Discussionmentioning
confidence: 99%